Public Communication Strategies in Urban Mass Transit: A Case Study of the BISKITA Campaign by the Bekasi Transportation Agency - Tin Hartini; Istiana Tiara Ramadhan; Abdul Haris (Fakultas Komunikasi, Sastra, dan Bahasa, 2025)
Public transportation systems are essential in addressing urban challenges such as traffic congestion, air pollution, and the demand for efficient mobility. In response to these issues, the City of Bekasi launched the BISKITA Trans Bekasi Patriot program to encourage public adoption of mass transit. Despite the program’s significance, limited research has examined how local governments communicate such initiatives to the public. This study aims to analyze the public communication strategy employed by the Transportation Agency of Bekasi in promoting the BISKITA program. Using a descriptive qualitative approach and the campaign component model, this research investigates the key stages of the campaign: communicator selection, message development, media channels, audience targeting, and feedback mechanisms. Data were collected through interviews, document analysis, and field observations. Findings indicate that the agency adopted a collaborative communication strategy, leveraging a mix of digital and traditional media, including Instagram, local radio, and on-the-ground outreach. The campaign emphasized two-way communication by fostering direct engagement with the public, rather than relying solely on one-way information dissemination. However, the study also identified constraints such as limited human resources and budgetary restrictions affecting content production and distribution. This research contributes to the understanding of effective communication in urban transportation campaigns and highlights the need for better resource planning and sustained public engagement strategies in local government initiatives.